Plasma Exosome-Derived SENP1 May Be a Potential Prognostic Predictor for Melanoma - Hu, Hejuan; Ling, Bai; Shi, Yuhan; Wu, Haohao; Zhu, Bingying; Meng, Yiling; Zhang, Guo-Ming (Frontiers in Oncology, 2021)
Objective: To evaluate plasma exosome-derived SUMO-specific protease (SENP)1 levels and assess their prognostic value in melanoma. Patients and Methods: We extracted exosomes from the plasma of 126 melanoma patients, and identified them with transmission electron microscopy, nanoparticle tracking analysis and western blotting. The plasma exosome-derived SENP1 levels of melanoma patients and healthy controls were detected with ELISA. Results: Plasma exosome-derived SENP1 levels in melanoma patients were significantly more upregulated than in healthy controls (P < 0.001). Plasma exosome-derived SENP1 levels in melanoma patients with tumor size >10 cm, located in the mucosa or viscera, with Clark level IV/V, with lymph node metastasis, and TNM stages IIb–IV were significantly higher than in patients in with tumor size <10 cm, located in the skin, with Clark level I–III, without lymph node metastasis, and TNM stages IIb–IV (all P < 0.05). Disease-free survival (DFS) and overall survival (OS) were worse in melanoma patients who had higher plasma exosome-derived SENP1 levels than lower plasma exosome-derived SENP1 levels (both P < 0.001). Area under the receiver operating characteristic curve (AUROC) of plasma exosome-derived SENP1 for predicting 3-year DFS of melanoma patients was 0.82 [95% confidence interval (CI): 0.74–0.88], with a sensitivity of 81.2% (95% CI: 69.9–89.6%) and specificity of 75.4% (95% CI: 62.2–85.9%). The AUROC of plasma exosome-derived SENP1 for predicting 3-year OS of melanoma patients was 0.76 (95% CI: 0.67–0.83), with a sensitivity of 95.7% (95% CI: 85.5–99.5%) and specificity of 62.0% (95% CI: 50.4–72.7%). Conclusions: Melanoma patients with higher plasma exosome-derived SENP1 levels had worse DFS and OS. The plasma exosome-derived SENP1 levels may be a potential prognostic predictor for 3-year DFS and 3-year OS of melanoma.